The distribution of memories for popular songs in old age: An individual differences approach. (July 2016) - Zimprich, Daniel; Wolf, Tabea
The purpose of the present study was threefold: We first aimed to replicate the finding that songs that were popular during people's adolescence are remembered best. Secondly, we extended prior research by modelling individual differences in the location and the variance of individual distributions of memories for popular songs. The third aim was to introduce explanatory variables that may account for these differences. The sample for the present study comprised 90 participants aged between 58 and 86 years. Participants listened to excerpts of 31 songs that ranked in the top three of the German charts between 1954 and 1997. If participants recognized a song, they rated their preference for and the frequency of listening to the song. Participants recognized a greater amount of songs that had been popular when they were between 10 and 30 years old. Musical preferences during participants' youth and today as well as the preferences for and the frequency of listening to the songs used in the present study accounted for individual differences in the distribution of memory for popular songs. An individual differences approach is a useful way to understand why popular songs (and probably other memories) from one's youth are remembered better.